Evaluation of the relationship between physical activity level and functional capacity, depression and quality of life in patients with knee osteoarthritis (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effects of physical activity level on functional capacity, depression and quality of life in patients with knee osteoarthritis (OA).Materials and Methods: Seventy nine patients who were diagnosed with knee OA according to ACR (American College of Rheumatology) criteria who applied to Inonu University, Turgut Özal Medical Center, Department of Physical Medicine and Rehabilitation, were included in the study. Radiological stage of knee osteoarthritis was evaluated according to the Kellgren Lawrence score. The patients were divided into two groups as Inadequate Activity Group (IAG) and Physically Active Group (PAG) according to their answers to the International Physical Activity Questionnaire (IPAQ-SF). Patients were evaluated using the ShortForm 36 (SF-36) questionnaire, the Beck Depression Inventory (BDI), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC).Results: WOMAC physical function scores were lower on PAG. The average BDI score of PAG was significantly lower than IAG. The average SF-36 scores in PAG were found to be significantly higher when compared with the IAG (p 0.05).Conclusion: Increased physical activity in patients with knee osteoarthritis; It has positive effects on functional capacity, depression and quality of life.